Quantitative logics for directed evolution of an asexual population - Kangbien Park (PLoS ONE, 2026)
Directed evolution of asexual populations is expected to offer a wide range of benefits to humanity. Achieving efficient directed evolution (DE) requires a quantitative formulation of experimental methodologies—or logics—that can address potential challenges throughout the evolutionary process. In this article, ten logics designed for resolving such difficulties when performing DE are introduced. To illustrate their application, a hypothetical scenario is considered in which an imaginary asexual population limb evolves into a wing, using a matrix-based discretization method to represent the trait of interest. Specifically, based on the operator model, fifty simulation iterations with logics applied and thirty iterations without logics were done. The results indicate that the introduced logics can accelerate the evolutionary process by roughly 2.6 times, while achieving an average accuracy for reaching the objective trait of approximately 82%. Based on these findings, key considerations for implementing quantitative logic-based DE are discussed, along with approaches for improving alignment between the final outcome and the target reference trait. Moreover, factors that could contribute to making the quantitative logic-based DE process more practical and rigorous are also examined.